Relationship between body condition score and subcutaneous fat and muscle area measured by ultrasound in Pelibuey ewes - Herrera, N. F. O. Robertos, A.J. Chay-Canul, R. A. Garcia-; Cruz, Ulises Macias-; Pérez, Ricardo Vicente-; Villalvazo, Víctor M. Meza- (Emirates Journal of Food and Agriculture, 2019)
Abstract